Relação entre o Tinnitus Handicap Invetory, acufenometria e avaliação visual analógica na avaliação do zumbido - Nascimento, Islan da Penha (2015)
Tinnitus is the perception of sound in the absence of a sound source. Occurring between 10-15% of the world population still needs better understanding of its pathophysiology, clinical comorbidities and more effective treatments. To this end, a better standardization of the use of evaluation methods in researches is required. This study aims the choice of most appropriate and easier use and interpretation methods. Initially an article in the form of a systematic review was performed in order to establish which evaluation methods of tinnitus are currently being used by scientific works. The aim of their uses was also identified. The THI, the EVA and the acuphenometry were the most used methods in 24 articles reviewed. The evaluation of therapy for tinnitus was the most frequent verified goal. A second article was performed to carry out a comparative analysis of these three methods. It was the THI, EVA (bother) and acuphenometry (loudness and pitch) in 44 patients with chronic tinnitus. A positive correlation of moderate intensity between them was found, being stronger between THI and VAS. It is concluded that the three evaluated tests keep moderate relation to each other. this should be taken into account when comparing with each other the results of different studies. The results of THI and EVA are be more strongly compared. Other future studies with more patients and more homogeneous sample can bring more contribution to the topic.